Exploration of Endophytic Fungi and Their Bioactive Potential Isolated from the Medicinal Plant Adhatoda vasica - Prodip Kumar Baral; Farhana Afroz; Nadira Begum; Satyajit Roy Rony; Suriya Sharmin; Fatema Moni; Shammi Akhter; Sakina Sultana; Mohammad Hossain Sohrab* (Iranian Society of Pharmacognosy, 2024)
Background and objective: The plants with pharmacological potential host potential endophytic fungi having metabolic interaction. Adhatoda vasica Nees, a well-reputed medicinal plant in Asia, has very few investigations on the plant's endophytic fungi available. This study reports the isolation, identification, and bioactive potential determination of the endophytes from the leaf and stem of the plant growing in Bangladesh. Methods: A protocol for fungus isolation was followed, including the significant steps: sample collection, surface sterilization, cultivation, preliminary selection, and purification. The fungal species were identified by morphological and molecular features, and then, small-scale cultivation followed solvent treatment (chloroform) to extract secondary metabolites. The extract's cytotoxic, antimicrobial, and antioxidant activities were determined by brine shrimp lethality bioassay, disc diffusion method, and DPPH free radical scavenging activity, respectively. Results: Eight endophytic fungi were isolated and identified: four Fusarium sp., two Colletotrichum sp., one Phacidiopycnis sp., one Lasiodiplodia sp. Genome sequence confirmed two novel fungi from the plant: Fusarium solani (OR414980) and Colletotrichum gloeosporioides (OR420097). In bioactivity testing, the fungi from the stem exhibited better activity than the leaf fungi. Among the eight fungi, Lasiodiplodia sp. showed the highest and most significant potential in each bioactivity test. Its extract (100 µg/disc) was approximately 80% susceptible against Gram-negative and Gram-positive bacteria and a fungus A. flavus compared to references (30 µg/disc). The fungus's LC50 (4 h) was 0.45 µg/mL, whereas vincristin sulfate showed nearly half.  Conclusion: The study recorded uncommon fungi of four genera from A. vasica; some showed remarkable bioactivity.